Bispidine Copper(II) compounds: effects of the rigid ligand backbone - Comba, Peter; Lienke, Achim (Inorganic chemistry, 2001)
Approximative density-functional theory calculations indicate that the tetradentate ligand L (L = 2,4-bis-(2-pyridyl)-3,7-diaza-[3.3.1]-bicyclononane) enforces an unusual and strong binding of a co-ligand (substrate) to a copper(II) center. The co-ligand in [Cu(L)(Cl)]+ completes a square-pyramidal coordination around copper(II) and binds in the equatorial plane rather than on the apical position. This configuration is a stable geometric isomer for the model complex [Cu(NH3)2(imine)2(Cl)]+, but it is disfavored by approximately 10 kJ mol-1 and not commonly observed for CuN4 chromophores with a monodentate co-ligand. The equatorial coordination increases the bond energy of the copper(II)−chloride bond by approximately 80 kJ mol-1, and similar results are expected for other copper(II)−L-substrate complexes, some of which show strong catalytic activity or unusual stability. Despite the enforced configuration, L does not impose significant steric strain on the copper(II) center but is well preorganized for the Jahn−Teller labile ion in this unusual geometry. The preorganization extends to the orientation of the pyridine donors (torsion angle around the copper−pyridine bond), and this seems to be of importance in the reactivity of the copper−L complexes and their derivatives.